Finansowanie przedsiębiorstwa w kryzysie - Duliniec, Aleksandra (Financing Company in Crisis, 2007)
Deep restructuring of activities and access to new capital are essential for companies in financial it sources of turnaround financing are very limited in such conditions. High business and risks, low profitability, lack of financial liquidity and danger of bankruptcy do not attract many investors. Some private equity funds looking for high risk and high potential return investments may provide companies in financial crisis not only with capital but also with managerial support necessary to implement recovery programmes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 136-143